On Availability for Blockchain-Based Systems - Weber, Ingo; Gramoli, Vincent; Ponomarev, Alex; Staples, Mark; Holz, Ralph; An Binh Tran; Rimba, Paul (2017 IEEE 36th Symposium on Reliable Distributed Systems (SRDS), 2017)
Blockchain has recently gained momentum. Startups, enterprises, banks, and government agencies around the world are exploring the use of blockchain for broad applications including public registries, supply chains, health records, and voting. Dependability properties, like availability, are critical for many of these applications, but the guarantees offered by the blockchain technology remain unclear, especially from an application perspective. In this paper, we identify the availability limitations of two mainstream blockchains, Ethereum and Bitcoin. We demonstrate that while read availability of blockchains is typically high, write availability - for transaction management - is actually low. For Ethereum, we collected 6 million transactions over a period of 97 days. First, we measured the time for transactions to commit as required by the applications. Second, we observed that some transactions never commit, due to the inherent blockchain design. Third and perhaps even more dramatically, we identify the consequences of the lack of built-in options for explicit abort or retry that can maintain the application in an uncertain state, where transactions remain pending (neither aborted nor committed) for an unknown duration. Finally we propose techniques to mitigate the availability limitations of existing blockchains, and experimentally test the efficacy of these techniques.